UJI COBA PENGELUARAN KAYU DI HUTAN TANAMAN PULAU LAUT DENGAN SISTEM KABEL LAYANG P3HH20 YANG DISEMPURNAKAN - Dulsalam Dulsalam; Djaban Tinambunan (Jurnal Penelitian Hasil Hutan, 2002)
log extraction in undulating forest areas needs special attention. Forest Products Research Centre has made improvement on P3HH20 skyline system designed for extracting log on undulating area. The equipment consists of three main parts such as power machine unit, wire rope and its auxillary and carriage intended to guide log movement. At the first time, the capacity of the equipment was only 0.308 m3/round trip. In 1998, the equipment was improved and then in 1999 was tried to extract logs in forest plantation of PT Inhutani II. Pulau Laut. South Kalimantan. The choice of the location was done purposively. The objective is to prove whether the impoved P3HH20 skyline system is suitable for extracting log in plantation forest area having undulating terrain. The research results showed that:1. The use of improved P3HH20 skyline cable system for log extraction in plantation forest Pulau Laut provides promising suitability with still relatively low productivity,2. log diameter extracted ranged from 17 to 43 cm with an average of 23 cm while log length extracted ranged from 8 m to 12 m with an average of 11 m.3. log volume extracted varied from 0.026 to 0.309 m3/round trip with an average of 0.160 m3/round trip.4. Effective log extraction productivities ranged from 1.404 to 2.810 m3 (hour with an average of 1.980 m3/hour while the total log extraction productivities varied from 0.485 to 1.080 m3/hour with an average of 0.885 m/hour.5. The average of log extraction cost was Rp 23.572/m3.6. To increase log extraction productivity. it is suggested that further improvement on ballast and endless cable need to be done. as well as further trial infield operations.